Spot urine pancreolauryl test for use in infancy. Issue 3 (March 1995) - Green, M R; Austin, S; McClean, P; Jolliffe, S; Weaver, L T
Abstract : As a simple non-invasive test of possible pancreatic insufficiency 10 healthy infants, 13 infants with cystic fibrosis, and nine infants with unexplained diarrhoea and failure to thrive were given an emulsion containing fluorescein dilaurate and mannitol by mouth. A spot urine specimen was collected and results expressed as urinary fluorescein to mannitol ratios. Sensitivity of the test was 96% and specificity was 95%.